Faktor-Faktor yang Mempengaruhi Kemiskinan di Provinsi Kalimantan Timur - Indhira Warlinasari; Irwan Gani; Muliati, Se Mulliati (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
The research entilted “Factors Affeting Poverty Rate in East Kalimantan Province”. This study aimed to determine the effect of open unemployment, the effect of government spending for education field, and  government spending for health field to poverty in East Kalimantan Province. The data used in research data is from Central Bureau of Statistics in East Kalimantan Province in the years 2003-2017. Analysis method of this research is Multiple Linear Regression. The software used to perform the analysis is IBM SPSS version 24.00. The analysis showed that government spending for education fields and government spending for health fields to poverty in East Kalimantan Province was a negative and significant effect, and open unemployment to poverty in East Kalimantan Province was a positive effect and not significant.        .